Are serum thyroid hormone, parathormone, calcium, and vitamin D levels associated with lumbar spine degeneration? A cross-sectional observational clinical study. - Dash, Pratap Kumar; Panda, Madhusmita; Sahoo, Duryodhan (Student’s Journal of Health Research Africa, 2025)
Background Lumbar spine degeneration (LSD) is a major contributor to chronic low back pain, particularly among older adults, leading to reduced quality of life and functional impairment. While mechanical stress and aging are established contributors, the role of systemic metabolic and hormonal factors remains inadequately explored. This study evaluated the association of serum vitamin D, calcium, parathormone (PTH), and thyroid hormones with lumbar spine degeneration. Methods This cross-sectional observational study was conducted at Dharanidhar Medical College and Hospital, Keonjhar. A total of 100 participants aged ≥50 years were enrolled, comprising 50 patients with clinically and radiographically confirmed lumbar spine degeneration and 50 age- and sex-matched controls without spinal degeneration. The study population included 55 males and 45 females, with the majority belonging to the 60–69-year age group. Serum levels of 25-hydroxyvitamin D, total calcium, intact PTH, thyroid-stimulating hormone (TSH), and free thyroxine (free T4) were measured. Statistical analysis was performed using appropriate parametric and non-parametric tests, with p < 0.05 considered significant. Results Patients with lumbar spine degeneration demonstrated significantly lower mean serum vitamin D (18.5 ± 4.2 ng/mL) and calcium levels (8.2 ± 0.6 mg/dL) compared to controls (32.1 ± 3.5 ng/mL and 9.1 ± 0.5 mg/dL, respectively; p < 0.001). Serum PTH levels were significantly higher in the LSD group (75 ± 12 pg/mL) than in controls (40 ± 8 pg/mL; p < 0.001). No statistically significant differences were observed in TSH or free T4 levels between the two groups. Conclusion Vitamin D deficiency, hypocalcemia, and secondary hyperparathyroidism are significantly associated with lumbar spine degeneration, whereas thyroid hormone levels are not. Recommendations Early correction of these metabolic abnormalities may help improve spinal health and potentially slow degenerative progression. Further longitudinal and interventional studies are warranted to establish causality and therapeutic benefit.